European migration crisis of 2015 and its influence on Poland’s foreign policy in the period 2015–2018 (Economic and Political Thought, 2019)
The article discusses the influence of the European migration crisis onPoland’s foreign policy in the period 2015–2018. The research aims to answerthe question to what extent and level and under the influence of what factorsthe immigration crisis of 2015 had impact on the foreign policy of theRepublic of Poland. The first part of the article analyses the reasons and thecourse of the immigration crisis of 2015. The next part presents the evolutionof Poland’s stance on the immigration crisis. The final part of the articlecontains main conclusions.
Keywords: Poland’s foreign policy, immigration crisis, European Union, Visegrad Group